Essays on international capital flows - Mercado, Rogelio (Trinity College (Dublin, Ireland). Department of Economics, 2017)
The core of this thesis consists of three papers. Although independent, these papers highlight the importance of looking into foreign-driven capital flows in understanding the transition to and from various episodes of gross capital inflows as well as their impact on output and credit growth. Chapter 2 extends the literature on gross capital flows by looking into domestic factors that covary significantly with cross-country differences in the transitional likelihoods of moving between episodes of capital inflows. Applying a state-transition framework, we view states of gross capital inflows as “normal”, “surge”, and “stop”. Following Forbes and Warnock (2012a and 2012b), we identify extreme episodes for a sample of 55 advanced and emerging economies from 1980Q1 to 2014Q4. The empirical findings show that cross-country differences in transitional likelihoods are strongly associated with state-dependence variables such as duration and occurrence. There is evidence to suggest the presence of negative duration dependence on the transitional likelihood of moving between episodes such that the longer an economy spends in a given episode, the less likely it will exit that episode. However, duration and occurrence of total gross inflow episodes are also significantly correlated with domestic factors such as output volatility, de facto and de jure financial openness, and foreign reserves. Chapter 3 looks into the transition of a surge episode to a stop episode and differentiates between two types of surges, namely surges that end in stops and surges that end in normal episodes. Previous studies on capital flows show that surges end in output contraction, crises, and reversals of capital inflows. However, when one looks closely at the data, not all surges of gross capital inflows end in reversals or stops. In fact, more than half of surges end in normal episodes at least four quarters following the last surge quarter. The chapter looks into global and domestic factors that strongly correlate with the transition of surges to either stop or normal episodes (as well as which factors correlate with the magnitude of gross inflows for these two types of surges). The results show that the higher likelihood of experiencing surges ending in stops is significantly correlated with lower global risk aversion and with higher domestic output gap. Higher likelihood of surges ending in stops is significantly related with higher global growth for emerging economies, but with lower global growth for advanced economies. The results also indicate that surges ending in stops are different from surges ending in normal episodes. For instance, while global risk aversion and domestic credit are significant for both surges, larger gross capital inflows are significantly correlated with higher global commodity prices for surges ending in stops, but with lower commodity prices for surges ending in normal episodes. Therefore, not all surges are alike. Chapter 4 sets out to assess whether gross capital inflows to the Philippines are expansionary or contractionary in line with the model predictions and empirical findings of Blanchard et al. (2015). The results indicate that gross inflows are expansionary to output and credit growth. But contrary to the model predictions and empirical findings of Blanchard et al. (2015), we find that private bond inflows to the Philippines are expansionary. Bond inflows may have expansionary impact on output and credit growth if the exchange rate is managed, if the domestic capital market is underdeveloped, if the country receives small bond inflows, and if proceeds from debt issuance are channelled to productive investments. Similar to Blanchard et al. (2015), non-bond inflows have a positive overall impact on output and credit growth despite receiving relatively small foreign direct investment inflows.

Revised versions of Chapters 2, 3 and 4 are published as journal articles:

Chapter 2: Capital Flow Transitions: Domestic Factors and Episodes of Gross Capital Inflows, Emerging Markets Review, 38(1): 251-264, 2019. https://doi.org/10.1016/j.ememar.2019.02.002

Chapter 3: Not All Surges of Gross Capital Inflows are Alike, Journal of Economic Studies, 45(2): 326-347, 2018. https://doi.org/10.1108/JES-01-2017-0007

Chapter 4: Are Capital Inflows Expansionary or Contractionary in the Philippines? Journal of Asian Economics, 2020. https://doi.org/10.1016/j.asieco.2020.101176

Author's website https://sites.google.com/site/rogeliomercadojr/home
Keywords: Economics, Ph.D.; Ph.D. Trinity College Dublin